Clinical-epidemiological profile of accidents with venomous animals in a microregion of Minas Gerais, Brazil (Research, Society and Development, 2022)
Accidents with venomous animals are neglected health problems, especially in underdeveloped and developing countries. Misregistration of information makes it difficult to comprehend the real incidence of this morbidity. Thus, the objective of the study is to characterize the epidemiological and clinical profile of accidents with venomous animals in a microregion of Minas Gerais. This is an epidemiological observational study of retrospective, descriptive and quantitative analysis of accidents with venomous animals occurred in the microregion of Pedra Azul in the state of Minas Gerais from 2017-2020. There were 1817 accidents in the microregion during the study period. Most accidents occurred in 2018, distributed over the months. Comercinho was the county with highest incidence, and accidents occurred mostly in rural areas. Scorpion stings was the most frequent accident. Women were the most frequent victims and the economically active population (20-59 years) the most affected. The majority of victims were assisted within 1 hour after the accident and most of them were not administered antivenom serum therapy. Hands and feet were the most affected. Therefore, the importance of the results in the fortification of regional health surveillance is highlighted, as well as in encouraging the correct filling and feeding of the national database.